154
CHAPTER
5.
TAYLOR'S
FORMULA.
TAYLOR
SERIES.
Then,
(5.46) follows easily from (5.48)
and
(5.49), i.e.,
1
..
k
R =
~
he~f
If(k)(a)1
1
/
k
'
The
result
of
(5.47) is
obtained
immediately
from (5.46) using (5.44)1. D
The
convergence
and
smoothness
properties
of
the
Taylor series
expan-
sions
can
be
derived from
Theorem
4.4
and
Theorem
4.5:
Theorem
5.5.
Let
f(x)
be
an infinitely differentiable function, and let
T(x)
be
the Taylor series expansion
of
f (x) around the point a.
If
R is the radius
of
convergence
of
T(
x),
then
T(
x) is convergent, and therefore well defined,
on the interval
(a
- R, a + R). Moreover,
T(x)
is infinitely
many
times
differentiable on the interval
(a
- R, a + R).
We
note
that
Theorem
5.5 specifies
the
convergence
domain
of
the
Taylor
series
T(x),
but
does
not
imply
that
T(x)
=
f(x)
on
that
domain. Sufficient
conditions for
the
convergence
of
the
Taylor series expansion
T(x)
to
the
function
f (x)
are
given below.
Theorem
5.6.
Let
f(x)
be
an infinitely differentiable function, and let
T(x) = f
(x
~!a)k
jlk)
(a)
k=O
be
the Taylor series expansion
of
f(x)
around the point
a.
Let R
be
the radius
of
convergence
of
T(
x),
and let r such that 0 < r <
R.
If
lim
rn
sup
If(n)(z)1 = 0,
n--too
n!
zE[a-r,a+r]
(5.50)
then
T(x)
=
f(x),
V
Ix
-
al
::;
r.
Proof. Since r < R,
the
Taylor series
T(
x) is convergent for
any
x such
that
I x - a I
::;
r.
Recall from (5.43)
that
T (x) =
limn--too
P
n
(
X
).
Thus,
f(x)
-
T(x)
= lim
(f(x)
- Pn(x)) , V
Ix
-
al
::;
r.
(5.51)
n--too
Let
x E
[a
-
r,
a +
r]
arbitrary.
From
the
derivative form (5.3) for
the
Taylor residual,
it
follows
that
there
exists a
point
c between a
and
x such
that
( )
n+1
f(x)-Po(x)
=
x-a
f(n+1)
(c)
n
(n+1)!
.
(5.52)
----------------------
1 We implicitly assumed
that
f(k) (a)
=I
0, for k
:::::
O.
If
this
is
not
the
case,
the
proof of
Theorem
5.4 follows along
the
same lines, if we consider
that
If(k5(a)1
=
00,
if f(k)(a) =
O.
5.3.
TAYLOR
SERIES EXPANSIONS
155
Note
that
c E
[a
- r, a +
r],
since x E
[a
- r, a +
r].
Then,
I
In+1
n+1
If
(x) -
Po
(x) I = x - a
If
(n+
1
) (
c)
I < r
su
p I
f(n+
1
) (z ) I '
n (n+1)! -
(n+1)!
zE[a-r,a+r]
since
Ix
-
al
::;
r.
From
(5.50), we
obtain
that
lim
If(x)
- Pn(x) I =
0,
V x E
[a
- r, a +
r],
n--too
and
therefore
T(x)
=
limn--too
Pn(x) =
f(x),
for all
Ix
-
al
::;
r.
D
5.3.1
Examples
of
Taylor
series
expansions
The
Taylor series expansions
of
the
following functions
are
often used
in
practice:
In(1
+
x)
In
(1
-
x)
1
1+x
1
1-x
00
k
-
L~
=-x
2
3 4
, V x E
[-1,
1); (5.54 )
k=1
00
"'(_1)k
xk 2 3
L...t
=
1-
x + x - x + ... , V x E
(-1,1);
k=O
00
L xk = 1 + x + x
2
+ x
3
+ .
..
, V x E
(-1,
1).
k=O
(5.55)
All
these
Taylor series expansions are
around
0; for example, (5.53) corre-
sponds
to
(5.42) for
f(x)
=
eX
and
a =
O.
Note
that
(In
(1
x))' =
-l~x'
From
Theorem
4.5,
it
follows
that
the
Taylor series expansion
of
the
function
l~x
can
be
obtained
by differentiat-
ing
term
by
term
the
Taylor series expansion
of
the
function In
(1
-
x)
and
multiplying
the
result
by
(-1).
This
is, indeed,
the
case; see (5.54)
and
(5.55).
We conclude
by
analyzing
the
convergence
of
the
Taylor series for
eX
and
In(1+x).
Example:
The
Taylor series expansion
00
k
T(x)
=
L%,
k=O
(5.56)